365 nights in Hollywood - Wurtzel, Sol; Marshall, George; Faye, Alice 1915-1998 (Distributed exclusively by Englewood Entertainment, 1998)
Down-on-his-luck film director Jimmie Dale takes a job at a fly-by-night acting school. He is drawn into the plans of the school's owner to bilk a wealthy young man out of the funds he has supplied to shoot a movie starring pretty student Alice Perkins. But Jimmie hopes to bilk the bilkers by actually completing the movie as ostensibly planned.